Ugotavljanje razvoja specifičnih kompetenc za poučevanje plavanja pri praktikumu predmeta Plavanje 2 + 3 - Kapus, Jernej (Šport (Ljubljana), 2018)
The aim of the study was to obtain the development of the specific competencies for teaching swimming throughout the practicum of Swimming 2+3 course at Faculty of Sport, University of Ljubljana. Fifty-one students volunteered to participate in the study. They evaluated 19 specific competencies five times i.e. pre- and post- practicum and after theirs teaching practical sessions during the practicum. The Likert scale with five scores was use for evaluation the specific competencies. Considering the results obtained by student%s self-reflection, the majority of specific competencies (16 of 19) were improved through the practicum. It seemed that students needed more practice to improve the rest of them.
Keywords: plavanje; poučevanje plavanja; praktikum; raziskave; samorefleksija; šport